Exploring the pathogenesis of type 2 diabetes mellitus intestinal damp-heat syndrome and the therapeutic effect of Gegen Qinlian Decoction from the perspective of exosomal miRNA. (1st March 2022) - He, LiSha; Bao, Tingting; Yang, Yingying; Wang, Han; Gu, Chengjuan; Chen, Jia; Zhai, Tiangang; He, Xinhui; Wu, Mengyi; Zhao, Linhua; Tong, Xiaolin
Abstract: Ethnopharmacological relevance: Diabetes is a common, complex, chronic metabolic disease. A randomized, double-blind, placebo-parallel controlled clinical study has shown that Gegen Qinlian Decoction (GQD) can reduce glycosylated hemoglobin in type 2 diabetes mellitus (T2DM) intestinal damp-heat syndrome patients in a dose-dependent manner. Aim: To explore the pathogenesis of T2DM intestinal damp-heat syndrome and the therapeutic effect of GQD from the perspective of exosomal microRNA (miRNA). Methods: Eligible patients were selected and treated with GQD for 3 months to evaluate their clinical efficacy. Effective cases were matched with healthy volunteers, and saliva samples were collected. Exosomal miRNA was extracted from saliva and analyzed by chip sequencing. Subsequently, the function of the differential gene and the signal transduction pathway were analyzed using bioinformatics technology. Finally, three target miRNAs were randomly selected from the T2DM group/healthy group, and two target miRNAs in the T2DM before treatment/after treatment group were randomly selected for qPCR verification. Finally, we conducted a correlation analysis of the miRNAs and clinical indicators. The registration number for this research is ChiCTR-IOR-15006626. Results: (1) The expression of exosomal miRNA chips showed that there were 14 differentially expressed miRNAs in the T2DM group/healthy group, and 26 differentially expressed miRNAs in the T2DM before treatment/after treatment group. (2) Enrichment results showed that in the T2DM group/healthy group, it was primarily related to cell development, body metabolism, TGF-β, and ErbB signaling pathways. In the T2DM before treatment/after treatment group, it was mainly related to cellular metabolic regulation processes, and insulin, Wnt, and AMPK signaling pathways. (3) The qPCR verification showed that the expressions of hsa-miR-9-5p, hsa-miR-150–5p, and hsa-miR-216b-5p in the T2DM group was higher (P<0.05). Following GQD treatment, hsa-miR-342–3p and hsa-miR-221–3p were significantly downregulated (P<0.05). (4) hsa-miR-9-5p was positively correlated with BMI (P<0.05), and hsa-miR-150–5p was positively correlated with total cholesterol and triglycerides (P<0.05). The GQD efficacy-related gene hsa-miR-342–3p was positively correlated with the patient's initial blood glucose level (P<0.05), and hsa-miR-221–3p was positively correlated with total cholesterol and triglycerides (P<0.05). Conclusion: The exosomal miRNA expression profile and signaling pathways related to T2DM intestinal damp-heat syndrome and the efficacy of GQD were established, which provides an alternative strategy for precision traditional Chinese medicine treatment. Graphical abstract: Image 1